Atuação do Estado no desenvolvimento econômico: a inovação tecnológica como eixo estruturante do desenvolvimento do Brasil - Benfatti, Fábio Fernandes Neves (2017)
This thesis studies the State’s actuation, aiming to investigate and analyze how Law influences the economic development. Law is focused as a social phenomenon and development is based on the fundamental objectives set forth in the Federal Constitution of 1988. It’s undeniable that technological innovation is essential in the new development matrix and in the new cycles. In this way, it underpins the economic development, being essential for the advancement of humanity, using Joseph Schumpeter’s economic theory: the creative destruction. In this sense, it presents itself as the structuring axis of the guarantee of economic development, which includes the construction of a free, just and solidary society, reducing social inequalities, promoting the benefit of all, based on the dignity of the human person, sovereignty, citizenship and social values of work, achieving an economic development built on free competition, consumer protection and the pursuit of full employment, and rescuing development in countries of late modernity.